INOVASI DAN PENGEMBANGAN DESA UNGGULAN STUDY KASUS PADA DESA GUNUNGGEMPOL KECAMATAN JUMO KABUPATEN TEMANGGUNG - Wedya Ardhini; Meidi Syaflan (Jurnal Riset Manajemen Akuntansi Indonesia, 2023)
The Village Government as the spearhead of national government policies must be able to arouse local potential in accordance with its function in carrying out the autonomy granted. This research uses qualitative deskriptif methods with research objects in Gununggempol Village, Jumo District,Temanggung Regency. From the results of the study, it can be concluded that Gununggempol Village, has implemented various development innovations based on nature preservation. Synergy of development is planned and implemented so that the existing concept of natural preservation can be implemented throughout the village consistently through a systematic process that is sustainable with commitment from all village stakeholders. On the results of the study, the Gununggempol Village Government recommends that it better involve the younger generation of villages in every village development planning deliberation and adopt the aspirations of the younger generation to develop village development. As a means for human resources development, especially in the younger generation, the Village Government can determine the priority of using village funds through increasing human resources capacity and also expected to improve the fissibility of planning, implementation, control, supervision and evaluation of the use of village financial resources.